2015
DOI: 10.1155/2015/928301
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Anterior Cruciate Ligament Injury and Osteoarthritis of the Knee

Abstract: Anterior cruciate ligament (ACL) tears are a common injury, particularly in the athletic and youth populations. The known association between ACL injury and subsequent osteoarthritis (OA) of the knee merits a more in-depth understanding of the relationship between the ACL-injured knee and osteoarthritis. ACL injury, especially with concomitant meniscal or other ligamentous pathology, predisposes the knee to an increased risk of osteoarthritis. ACL insufficiency results in deterioration of the normal physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 105 publications
2
85
0
2
Order By: Relevance
“…For example, in ACL injuries, concomitant meniscal or chondral injuries, post-operative excessive musculoskeletal loading, high BMI and inadequate strength training can all result in early osteoarthritis (19)(20)(21). In our study, patients who underwent previous knee surgery had no reported complications necessitating re-operation or revision surgeries on their follow-up visits (longest follow-up being up to 8 years after TKA).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in ACL injuries, concomitant meniscal or chondral injuries, post-operative excessive musculoskeletal loading, high BMI and inadequate strength training can all result in early osteoarthritis (19)(20)(21). In our study, patients who underwent previous knee surgery had no reported complications necessitating re-operation or revision surgeries on their follow-up visits (longest follow-up being up to 8 years after TKA).…”
Section: Discussionmentioning
confidence: 99%
“…Lateral tibial condylar lesions were associated with RR=3.264(95% CI of 1.253 -8.503).. Chondral lesions of patella(14.2%), Trochlea (4.7%)& Lateral femoral condyle( 5.7%) though present, didn't have significant association with delay in surgery. Our observations in 106 patients have limitations in throwing light to association of chondral changes in patella, trochlea and lateral femoral condyle, as compared to some investigators 4,[25][26][27][28] , as the numbers in subtypes were minimal for statistical association. Delay in surgery was also found to have significant association with the presence of intraarticular knee lesions and their number (<3lesions />3 lesions) RR 1.177(CI 1,027-1.349),P-.02 .…”
Section: Discussionmentioning
confidence: 65%
“…Despite a 'typical' mechanism of injury leading to ACL rupture [6][7][8] , poor rate of initial diagnosis, delay in surgery & its consequences are extremely common [9][10][11] . Concurrent Meniscal and Chondral Injuries in ACL injured knees has been reported by many authors [12][13][14][15][16][17][18][19][20][21] and remains a major cause of concern and prognostic factor in long term results [3][4][5] . Many studies have tried to associate delay in surgery to chondral & meniscal lesions necessitating additional procedures during ACL reconstruction surgery.…”
Section: Introductionmentioning
confidence: 99%
“…ACL injury, especially with concomitant meniscal or other ligamentous pathology, predisposes the knee to an increased risk of OA. Alone ACL reconstruction has not been shown to reduce the risk of future OA; weight management, avoidance of excessive musculoskeletal loading and strength training are further important strategies [5].…”
Section: Introductionmentioning
confidence: 99%